Sequence stratigraphy of the Scottish Laurentian margin and recognition of the Sauk megasequence - Raine, R; Smith, P (Co-published by AAPG and Shell, 2013)
The Cambrian?Ordovician succession of northwestern Scotland represents a fragment of a once-continuous southeastern Laurentian margin stretching between western Newfoundland and eastern Greenland. The subdivisions of the Sauk megasequence are recognized within the Scottish succession for the first time. The Sauk I supersequence corresponds to deposition of the Ardvreck Group, which is composed of a succession of arkoses, quartz arenites, and siltstones. The overlying Sauk II and III supersequences are represented by carbonates of the Durness Group. Within the Durness Group, several smaller sequences can be identified (interpreted as third order). The Sauk II supersequence can be divided into two sequences of 83- and 75-m (272- and 246-ft) thickness. These may correlate with Cambrian grand cycles recognized in other parts of Laurentia. The Sauk III supersequence contains four smaller sequences, some of which correlate with sequences observed in western Newfoundland. The top of the Sauk megasequence is not observed because of truncation of the available section by a thrust fault.